Curcumin-artemisinin coamorphous solid: Xenograft model preclinical study - Mannava, M. K. Chaitanya; Suresh, Kuthuru; Bommaka, Manish Kumar; Konga, Durga Bhavani; Nangia, Ashwini (Pharmaceutics, 2018)
Curcumin is a natural compound present in Indian spice turmeric. It has diverse pharmacological action but low oral solubility and bioavailability continue to limit its use as a drug. With the aim of improving the bioavailability of Curcumin (CUR), we evaluated Curcumin-Pyrogallol (CUR-PYR) cocrystal and Curcumin-Artemisinin (CUR-ART) coamorphous solid. Both of these solid forms exhibited superior dissolution and pharmacokinetic behavior compared to pure CUR, which is practically insoluble in water. CUR-ART coamorphous solid showed two fold higher bioavailability than CUR-PYR cocrystal (at 200 mg/kg oral dose). Moreover, in simulated gastric and intestinal fluids (SGF and SIF), CUR-ART is stable up to 3 and 12 h, respectively. In addition, CUR-PYR and CUR-ART showed no adverse effects in toxicology studies (10 times higher dose at 2000 mg/kg). CUR-ART showed higher therapeutic effect and inhibited approximately 62% of tumor growth at 100 mg/kg oral dosage of CUR in xenograft models, which is equal to the positive control drug, doxorubicin (2 mg/kg) by i.v. administration.

Entacapone: improving aqueous solubility, diffusion permeability, and cocrystal stability with theophylline - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Suresh, Kuthuru; Gunnam, Anilkumar; Nangia, Ashwini (Crystal Growth & Design, 2018)
Cocrystallization is a well-established technique to improve the solubility, bioavailability, and stability of active pharmaceutical ingredients (APIs) but permeability and diffusion rate control via cocrystals is relatively less well studied, and the exact role of coformers in influencing the diffusion rate of drug cocrystals is still not fully understood. The aqueous solubility and permeability diffusion of Entacapone, ETP, a Biopharmaceutical Classification System (BCS) Class IV drug of low solubility and low permeability, with Generally Regarded as Safe (GRAS) coformers has been studied. Fixed stoichiometry cocrystals of ETP with acetamide (ACT, 1:1), nicotinamide (NAM, 1:1), isonicotinamide (INAM, 1:1), pyrazinamide (PYZ, 1:1), and isoniazid (INZ), 1:1) were prepared by solvent-assisted grinding. Theophylline (THP) resulted in a cocrystal hydrate (ETP-THP-FIYD 1:1:1). The cocrystals were structurally characterized by single crystal and powder X-ray diffraction, DSC and TGA thermal measurements, and IR and NMR spectroscopy. Solubility and dissolution rate showed that there is a correlation between cocrystal stability and solubility governed by the heteromeric N-H center dot center dot center dot O, O-H center dot center dot center dot N, and O-H center dot center dot center dot O hydrogen bonds and conformational changes of ETP in cocrystal structures. ETP-THP-HYD and ETP-PYZ exhibit faster dissolution rate and high solubility and they are stable in phosphate buffer medium compared to the other cocrystals which dissociate partially during solubility experiments. Diffusion rates in a Franz cell showed that the stable and high solubility ETP-THP-HYD cocrystal has good permeability. Given that stability, solubility, and permeability are in general inversely correlated, the entacapone-theophylline hydrate cocrystal is a unique example of the thermodynamically stable cocrystal exhibiting high solubility and high permeability.

Improved stability of tuberculosis drug fixed-dose combination using isoniazid-caffeic acid and vanillic acid cocrystal - Battini, Swapna; Mannava, M. K. Chaitanya; Nangia, Ashwini Kumar (Journal of Pharmaceutical Sciences, 2018)
The classic fixed-dose combination (FDC) of 4 tuberculosis drugs, namely rifampicin (RIF), isoniazid (INH), pyrazinamide (PZA), and ethambutol dihydrochloride (EDH) has the twin issues of physical stability and RIF cross-reaction in the 4-FDC. The major reason for these quality issues is the interaction between RIF and INH to yield isonicotinyl hydrazone in drug tablets. Pharmaceutical cocrystals of INH with caffeic acid (CFA) (PZA + EDH + RIF + INH-CFA cocrystal) and vanillic acid (VLA) (PZA + EDH + RIF + INH-VLA cocrystal) are able to stabilize the FDC formulation compared with the reference batch (PZA + EDH + RIF + INH). Stability studies under accelerated humidity and temperature stress conditions of 40°C and 75% relative humidity showed that the physical stability of the cocrystal formulation was superior by powder X-ray diffraction and scanning electron microscopy analysis, and chemical purity was analyzed by high-performance liquid chromatography. Changes in the composition and structure were monitored on samples drawn at 7, 15, 22, and 30 days of storage. FDC-INH-CFA cocrystal batch exhibited greater stability compared with FDC-INH-VLA cocrystal and FDC reference drug batches. The superior stability of INH-CFA cocrystal is attributed to the presence of stronger hydrogen bonds and cyclic O−H⋯O synthon in the crystal structure.

Co amorphous valsartan nifedipine system: Preparation, characterization, in vitro and in vivo evaluation - Lodagekar, Anurag; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Yadav, Balvant; Chella, Naveen; Nangia, Ashwini K.; Shastri, Nalini R. (European Journal of Pharmaceutical Sciences, 2019)
Co amorphous systems are supersaturated drug delivery systems which offer a basic platform for delivery of multicomponent adducts (combination of more than one active pharmaceutical ingredient (API)) and/or as a fixed dose combination therapy, in addition to their potential to improve the apparent solubility, dissolution rate and ultimately bioavailability of poorly water soluble APIs. In the present work, a new drug-drug co amorphous system namely valsartan-nifedipine was prepared by quench cooling technique. Prepared co amorphous system was characterized for its solid state behavior with the help of Fourier Transform Infrared spectroscopy (FTIR), Differential Scanning Calorimetry (DSC) and Powder X Ray Diffractometry (PXRD). The optimized co amorphous system was stable for 1 month when exposed to accelerated stability condition (40 +/- 2 degrees C and 75 +/- 5% RH). The improved stability of amorphous nifedipine in co amorphous system was attributed to improved miscibility and intra and intermolecular non-covalent interactions mainly due to presence of hydrogen bonding between valsartan and nifedipine which was studied by FTIR analysis. Co amorphous systems were evaluated by mainly in vitro dissolution and in vivo benefit. In vitro dissolution study showed nearly 5.66 folds and 1.61 folds improvement which was translated to 3.63 and 2.19 times enhancement in vivo C-max for nifedipine and valsartan respectively.

Cocrystals, salts, and supramolecular gels of nonsteroidal anti inflammatory drug niflumic acid - Mittapalli, Sudhir; Mannava, M. K. Chaitanya; Sahoo, Rasmita; Nangia, Ashwini (Crystal Growth & Design, 2019)
Niflumic acid (NFA) is a nonsteroidal anti-inflammatory drug (NSAID) classified under the BCS (Biopharmaceutical Classification System) Class II category of poor aqueous solubility and high permeability. In an attempt to improve the physicochemical properties of NFA, particularly solubility and dissolution rate by cocrystallization and salt formation, cocrystals of NFA were prepared with caprolactam (CPR, 1:1) and 2-hydroxy pyridine (2HP, 1:1) as well as salts with piperazine (PIP, 1:0.5), benzenesulfonic acid (BSA, 1:1), benzyl amine (BZA, 1:1 and 2:2), and tyramine (TYA, 1:1). The new solid forms were characterized by powder X-ray diffraction, infrared spectroscopy, and differential scanning calorimetry and confirmed by single crystal X-ray diffraction. In the cocrystals NFA CPR and NFA-2HP, the cyclic amide of the coformer forms a dimer synthon through N-H center dot center dot center dot O hydrogen bonds and such dimers extend through O-H center dot center dot center dot O hydrogen bonds. In piperazine, benzyl amine, and tyramine salts, proton transfer occurs from the NFA to the basic nitrogen of the coformer, and in NFA BSA salt, the proton is transferred from benzenesulfonic acid to the pyridine nitrogen of NFA. In addition to the above salts and cocrystals, supramolecular gels of NFA-PIP and NFA-BZA salts are reported, which were obtained from nitrobenzene, methyl salicylate, menthol, and mesitylene solvents. These gels were studied by rheology. Solubility and dissolution rate of the novel solid forms (NFA CPR, NFA PIP, NFA BSA, and NFA TYA) in 20% EtOH water showed the best behavior for NFA-TYA salt with improvement of 42-and 54-times in solubility and dissolution rate compared to the reference drug. The remaining solids such as NFA-PIP, NFA-BSA salts, and NFA-CPR cocrystal exhibited improvement of 39-, 18-, 1.4-times in solubility and 7.8-, 10-, 2-times for dissolution rate.

Quantification of niclosamide polymorphic forms - a comparative study by Raman, NIR and MIR using chemometric techniques - Bhavana, Valmala; Chavan, Rahul B.; Mannava, M. K. Chaitanya; Nangia, Ashwini; Shastri, Nalini R. (Talanta, 2019)
Niclosamide, an anthelmintic drug recently repurposed for its activity against cancer, crystallizes into three solvated forms, two monohydrates (NHa, NHb) and one anhydrous (NAn) form. NAn is sensitive to pseudopolymorphic transformations that affect its dissolution and consequently, its bioavailability. NAn exhibits a polymorphic conversion to metastable monohydrate (NHa) form during high-energy milling in presence of poorly soluble solvents like water. It is hence very important to quantify polymorphic conversion from NAn to NHa, as water is a commonly used solvent during various processing like ball milling and wet granulation. This main objective of the study was to examine the feasibility of Raman, NIR and MIR spectroscopic techniques for identification and quantification of polymorphic forms of niclosamide in binary mixtures and multicomponent mixtures. Calibration models were developed and validated by vibrational spectroscopic techniques in binary mixtures of NAn and NHa and in multicomponent mixtures by chemometric techniques. These techniques were further used to identify and quantify NHa during ball milling, granulation and in presence of other polymorphic forms of niclosamide. Identification and quantification of pseudopolymorphs in binary and multicomponent mixtures with an acceptable recovery of 100.13-102.99% for Raman and 100.07-101.28% for NIR with low % RSD of 2.38-3.12 for both techniques were obtained. The % NHa determined during ball milling and granulation was similar by NIR and Raman. Raman spectroscopy however showed a greater advantage over other techniques in determining the NHa in presence of NHb due to significant difference in the spectral region of hydrates, when compared to NIR and MIR.
Keywords: Ball milling; Granulation; MSC; PLS; Polymorphic conversion; spectroscopy

Role of hydrogen bonding in cocrystals and coamorphous solids: indapamide as a case study - Allu, Suryanarayana; Suresh, Kuthuru; Bolla, Geetha; Mannava, M. K. Chaitanya; Nangia, Ashwini (Crystengcomm, 2019)
The stronger sulfonamide-pyridine (SO2NH2 center dot center dot center dot N-Py) and sulfonamide-carboxamide (SO2NH2 center dot center dot center dot O = C-NH) hydrogen bonds direct the formation of cocrystals, while the weaker sulfonamide-amine (SO2NH2 center dot center dot center dot N-H) hydrogen bond results in coamorphous products. IDP-PIP and IDP-ARG coamorphous solids exhibit remarkable stability under accelerated conditions.

Improving the dissolution rate of the anticancer drug dabrafenib - Rai, Sunil K.; Gunnam, Anilkumar; Mannava, M. K. Chaitanya; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Dabrafenib (DBF) is an anticancer drug with selective B-Raf (BRAF) inhibition activity. In 2013, DBF was approved by the U.S. Food and Drug Administration (US-FDA) as a dabrafenib mesylate salt (DBF center dot MS). Because of insolubility in aqueous medium, specifically at the pH 4-8 biorelevant range, DBF is a Biopharmaceutics Classification System (BCS) Class II drug (i.e., low solubility and high permeability). Therefore, screening of novel salts and cocrystals was carried out using Generally Recognized as Safe (GRAS) coformers. A total of 10 salts/cocrystals including the mesylate salt were found to be stable under the crystallization conditions. Among acidic coformers, methane sulfonic acid (MS) and saccharin (SACH) formed salts, while fumaric acid (FA), succinic acid (SA), and adipic acid (ADA) gave cocrystals. However, monoamines formed a monohydrate salt where the water molecule is hydrogen bonded with the aminopyrimidine moiety of DBF. The replacement of monoamines with ethylenediamine (EN) dislocated the water molecule near the free amine of EN in the crystal structure with a change in space group from triclinic (P (1) over bar) to monoclinic (P2(1)/n). Dissolution measurements at pH 1.2 (0.1 N HCl) showed that DBF center dot EN superset of H2O dissolved rapidly compared to the DBF.MS salt (the dissolution rate of DBF center dot EN superset of H2O and DBF center dot MS is 11 and 2 times faster than that of DBF). Structure-activity relationship analysis showed that bonding of the aminopyrimidine moiety with strong hydrogen bond synthons inhibited dissolution, whereas a loosely bound or free site at the aminopyrimidine moiety enhanced the dissolution rate. Finally, a cytotoxicity study was performed for DBF, DBF center dot MS, and DBF center dot EN superset of H2O, which showed that DBF center dot EN superset of H2O is safe for normal cells and yet equally potent against cancer cells. Crystal engineering of an improved formulation of dabrafenib center dot ethylenediamine hydrate is presented as a new anticancer drug.

Naftopidil molecular salts with improved dissolution and permeation - Mannava, M. K. Chaitanya; Dandela, Rambabu; Tothadi, Srinu; Solomon, K. Anand; Nangia, Ashwini K. (Crystal Growth & Design, 2020)
Naftopidil (NFPD) is a alpha 1 adrenoceptor antagonist drug. Low solubility and low permeability are the major drawbacks of this drug. The synthesis of multicomponent crystalline forms of this amine functional group drug with carboxylic acid coformers, both achiral and chiral acids, provides a solution to improve its solubility as well as permeability. Nine molecular salts were crystallized by liquid-assisted grinding followed by isothermal crystallization. Single-crystal X-ray diffraction analysis of the molecular salts showed that the structures are stabilized by strong N-H center dot center dot center dot O and O-H center dot center dot center dot O and weak C-H center dot center dot center dot O hydrogen bonds in the solid state. The bulk phase purity of new solid forms was confirmed by powder X-ray diffraction (PXRD), and the crystalline products were further characterized by IR spectroscopy and thermal analytical techniques (differential scanning calorimetry). The molecular salts exhibit superior dissolution rates compared to pure NFPD. However, during dissolution, NFPD showed decrease in concentration after 60 min for all salts due to precipitation. The supersaturation occurred due to salt disproportionation, which generates insoluble NFPD, as confirmed by PXRD of the residue. The salts reach high saturation concentration before 60 min, which is indicative of immediate release formulation to achieve fast onset of therapeutic activity. Moreover, the salts exhibit high saturation in phosphate buffer saline media and improved permeability compared to the pure drug. Finally, the D,L-malic acid racemate of NFPD shows enhanced dissolution and permeability compared to all other salts and pure NFPD.

Enhanced solubility, permeability, and tabletability of nicorandil by salt and cocrystal formation - Mannava, M. K. Chaitanya; Gunnam, Anilkumar; Lodagekar, Anurag; Shastri, Nalini R.; Nangia, Ashwini K.; Solomon, K. Anand (Crystengcomm, 2021)
Cocrystallization is a rational selection crystal engineering approach for the development of novel solid forms with enhanced physicochemical and mechanical properties. Nicorandil (NCR) is a niacinamide vitamin derivative used to treat angina pectoris. A binary solid form screen of NCR with homologous dicarboxylic acids afforded NCR-oxalic acid (NCR-OA, 1:1), NCR-fumaric acid (NCR-FA, 1:1), NCR-succinic acid (NCR-SA, 1:1), and NCR-suberic acid (NCR-SBA, 1:0.5). The binary solids were characterized by powder X-ray diffraction, IR and NMR spectroscopy, and DSC. NCR-FA and NCR-SBA were crystallized by slow evaporation from chloroform and toluene solvents, respectively. Single crystal X-ray diffraction confirmed that NCR-FA is a molecular salt, while NCR-SBA is a neutral cocrystal. NCR and the FA anion are connected via the robust carbovlate-pyridinium synthon, whereas in the NCR-SBA cocrystal, the components associate via the carboxylic acid- -pyridine synthon. The phase stability, solubility, dissolution rate, diffusion rate and tabletability studies have demonstrated that the binary solids exhibit improved physical and mechanical properties compared to the NCR drug. Specifically, the NCR-FA salt and NCR-SBA cocrystal have higher solubility, dissolution rate, and hardness at lower pressures, making the formulation suitable for tablet compression.

Entacapone polymorphs: crystal structures, dissolution, permeability, and stability - Bommaka, Manish Kumar; Mannava, M. K. Chaitanya; Rai, Sunil K.; Suresh, Kuthuru; Nangia, Ashwini K. (Crystal Growth & Design, 2021)
Entacapone (ETP) is a catechol-O-methyltransferase (COMT) drug used to treat Parkinson's disease. ETP is available in the marketplace under the brand name Comtan since 2010, and ETP form-I was first reported in a patent published in 2001. However, analysis of its Xray crystal structures and stability relationship of ETP polymorphs and their dissolution and permeability profile have not yet been reported. We crystallized two new conformational polymorphs of ETP from a water and acetone mixture and studied the structural origin of polymorphism and their phase transformations, stability, equilibrium solubility, dissolution, and permeability properties. The ETP molecule adopts different conformations in the polymorphic structures with slight changes in carbonyl and nitrile group orientations. Thermal analysis suggests that form-III and form-IV are enantiotropically related to form-I, which is the thermodynamically stable form at ambient conditions. In contrast, form-II is monotropically related to form-I. Equilibrium solubility, dissolution, and permeability studies show that form-II persists in the slurry medium and dissolves faster with a high flux rate compared to the stable form-I in phosphate buffer solution at 37 +/- 0.5 degrees C.

Fluorobenzoic acid coformers to improve the solubility and permeability of the BCS class IV drug naftopidil - Mannava, M. K. Chaitanya; Bommaka, Manish K.; Dandela, Rambabu; Solomon, K. Anand; Nangia, Ashwini K. (Chemical Communications, 2022)
Crystalline salts of the low solubility and low permeability drug naftopidil were investigated with mono-, di-, tri-, and tetrafluorobenzoic acids as coformers to show that 245TFBA (2,4,5-trifluorobenzoic acid) is the optimal salt with faster dissolution and high permeability, thereby opening the study of fluorinated coformers in pharmaceutical cocrystals and salts.

Inhibitory effect of curcumin-artemisinin co-amorphous on Tau aggregation and Tau phosphorylation - Dubey, Tushar; Sonawane, Shweta Kishor; Mannava, M. K. Chaitanya; Nangia, Ashwini K.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (Colloid and Surfaces B-Biointerfaces, 2023)
Tau is a natively unfolded microtubule-associated protein. Tau neurofibrillary tangles are one of the hallmarks of Alzheimer's disease. The post-translational modifications of Tau lead to its pathological state. Phosphorylation is the key post-translational modification associated with Tauopathy. Curcumin is a polyphenolic compound pre-sent in the rhizomes of Curcuma longa. Curcumin has been reported to have remarkable medicinal properties in several diseases, but its poor solubility limits its therapeutic potency. Artemisinin is a sesquiterpene lactone, which has been known sience ancient times for its applications as a treatment for various diseases such as malaria, cancer, autoimmune disease, etc. In the present study, the potency of crystalline curcumin, crystalline artemisinin, and Cur-Art co-amorphous dispersion were evaluated against Tau pathology. The in-vitro ThS/ANS fluorescence and electron microscopy results suggested that curcumin and Cur-Art efficiently inhibited Tau aggregation. Furthermore, exposure to curcumin and Cur-Art co-amorphous restored the impaired nuclear transport in formaldehyde-stressed cells. Curcumin was also found to modulate the phosphorylation of Tau, which indicated the neuroprotective potency. Thus, curcumin and Cur-Art co-amorphous exhibit therapeutic potential against Tau protein in Alzheimer's disease.
Keywords: artemisinin; curcumin; Phosphorylation; Tau Aggregation